Model Pembelajaran Predict-Discuss-Explain-Observe-Discuss-Explain Berbantuan Simulasi PhET untuk Meremidiasi Miskonsepsi Materi Fluida - Muhammad Luqman Hakim Abbas; Cindy Anatasya Prahesti (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Nahdlatul Wathan Mataram, 2024)
Understanding concepts is very required in physics learning. Many students have different understandings about scientific concepts, this term is usually called misconceptions. Misconceptions are a problem that must be addressed immediately, because they are one of the factors that cause students to experience difficulties in learning physics. This research aims to determine the effect of the PhET virtual simulation laboratory in overcoming students' misconceptions about fluids. This type of research is a Pretest-Posttest One Group Pre-Experimental design. The sample for this research was class XI science students at MA Al-Ihsan Kalikejambon Tembelang Jombang, taken using a purposive sampling technique. The test used is in the form of a multi-tier multiple choice test from a four-tier diagnostic test with a certainty response index (CRI) consisting of 20 items. The results of this study show that students' misconceptions decreased for all sub-concepts of fluid materials. Based on the statement explained previously, it can be concluded that physics learning based on virtual laboratories can correct students' misconceptions, especially in fluids